Analysis of a Geometrical-Stiffening Membrane Acoustic Metamaterial with Individually Tunable Multi-Frequencies - ZHAO, Junjuan; LI, Xianhui; THOMPSON, David; WANG, Yueyue; WANG, Wenjiang; ZHU, Liying; LIU, Yunan (Archives of Acoustics, 2021)
To realize a structure which can be conveniently tuned to multiple and wideband frequency ranges, a geometrical-stiffening membrane acoustic metamaterial (MAM) with individually tunable multiple frequencies is presented. The MAM is realized by a stacked arrangement of two membrane-magnet elements, each of which has a membrane with a small piece of steel attached in the centre. It can be tuned individually by adjusting the position of its compact magnet. The normal incidence sound transmission loss of the MAM is investigated in detail by measurements in an impedance tube. The test sample results demonstrate that this structure can easily achieve a transmission loss with two peaks which can be shifted individually in a wide low-frequency range. A theoretical consideration is analysed, the analysis shows that the magnetic effect related to this distance leads to a nonlinear attractive force and, consequently, nonlinear geometrical stiffening in each membrane-magnet element, which allows the peaks to be shifted. A reasonable design can make the structure have a good application prospect for low-frequency noise insulation where there is a need to adjust the transmission loss according to the spectrum of the noise source.